THE EFFECT OF THE COVID-19 PANDEMIC ON INFECTIOUS SOLID WASTE MANAGEMENT IN MOTHER AND CHILD HOSPITALS - I Ketut Yoga Sedana; Achmad Fajar; Eka Chandra Kusuma Wardhana; Arfiyani Zamanti; Dina Nofitria (Journal of Community Health and Preventive Medicine, 2022)
Coronavirus Disease 2019 (COVID-19) is a contagious disease that being caused from Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2). During COVID-19 pandemic, mother and child hospital carry their usual routine same as before the pandemic to give service for children and the mother. To increase the safety and the quality of service for the patient, the hospital increases the uses of medical personnel's protective equipment (PPE) and managing medical waste to adapt with the pandemic situation. Main purpose of the research is to examine how COVID-19 effected the number of the solid infectious medical waste being produced and the management of the waste itself on mother and child hospital. The research takes place on two mother and child hospital in Malang City with case study on both hospital by using quantitative research method for examining the impact that COVID-19 pandemic causes for the infectious solid medical waste number and the management of the waste itself. Analysis using the parametric T-Test shown 95% confidence interval. The result show their is a significant increase for the solid infectious medical waste that being produced by both Hospital. The first Hospital (A) show p-value 0,046 and the second hospital (B) p value is 0,00. The research concluded that COVID-19 pandemic effected the increase number of solid infectious medical waste produced in mother and child hospital and there is no difference for the waste management before and after COVID-19 pandemic.